Basophils from Cancer Patients Respond to Immune Stimuli and Predict Clinical Outcome - Heather J. Bax; Jitesh Chauhan; Chara Stavraka; Atousa Khiabany; Mano Nakamura; Giulia Pellizzari; Kristina M. Ilieva; Sara Lombardi; Hannah J. Gould; Christopher J. Corrigan; Stephen J. Till; Sidath Katugampola; et al. (Cells, 2020)
Basophils are involved in manifestations of hypersensitivity, however, the current understanding of their propensity for activation and their prognostic value in cancer patients remains unclear. As in healthy and atopic individuals, basophil populations were identified in blood from ovarian cancer patients (n = 53) with diverse tumor histologies and treatment histories. Ex vivo basophil activation was measured by CD63 expression using the basophil activation test (BAT). Irrespective of prior treatment, basophils could be activated by stimulation with IgE- (anti-FcεRI and anti-IgE) and non-IgE (fMLP) mediated triggers. Basophil activation was detected by ex vivo exposure to paclitaxel, but not to other anti-cancer therapies, in agreement with a clinical history of systemic hypersensitivity reactions to paclitaxel. Protein and gene expression analyses support the presence of basophils (CCR3, CD123, FcεRI) and activated basophils (CD63, CD203c, tryptase) in ovarian tumors. Greater numbers of circulating basophils, cells with greater capacity for ex vivo stimulation (n = 35), and gene signatures indicating the presence of activated basophils in tumors (n = 439) were each associated with improved survival in ovarian cancer. Circulating basophils in cancer patients respond to IgE- and non-IgE-mediated signals and could help identify hypersensitivity to therapeutic agents. Activated circulating and tumor-infiltrating basophils may be potential biomarkers in oncology.